A simple device for determination of incubation stages in eggs - van Paassen, Aad G; Veldman, Dick H; Beintema, Albert J (Wildfowl, 1984)
Many methods to determine the stage of incubation in birds’ eggs are available. In field studies of species which have boldly marked eggs, like waders, only those methods using floating characteristics are practicable. In order to standardize methods, and to obtain comparable results from different researchers, we developed an ’incubometer’, and calibrated it for the Lapwing Vanellus vanellus (based on 45 nests), and the Black-tailed Godwit Limosa limosa (based on 11 nests).